Gymnema phuquocense (Apocynaceae, Asclepiadoideae), a new species from Vietnam - Thu Ha Bui; Ngoc Han Le; The Bach Tran (PhytoKeys)
A new species of Gymnema from Vietnam – G. phuquocense – is described, illustrated, and compared with the similar G. yunnanense. Gymnema phuquocense differs from G. yunnanense by the length of peduncle (3–4 mm vs. 10–13 mm), hairs on corolla lobe margin (absent vs. present), shape of seed (broadly ovate vs. ovate-oblong), shape of scale with 2 prominent longitudinal ridges on corolla tube (lanceolate vs. linear), and length of seeds (9–10 mm vs. 13–15 mm). A diagnostic key of the Gymnema species in Vietnam is also provided.